Disease burden of viral hepatitis A, B, C and E: A systematic analysis. Issue 12 (18th August 2020) - Liu, Zhenqiu; Shi, Oumin; Zhang, Tiejun; Jin, Li; Chen, Xingdong
Abstract: Viral hepatitis has been recognized as a leading cause of deaths worldwide. We aimed to analyse the disease burden of viral hepatitis at the global, regional and national levels. We collected the data of death number, mortality rate, and disability‐adjusted life years (DALYs) of viral hepatitis by sex, age, geography and type of disease from the Global Health Data Exchange platform. Estimated average percentage change (EAPC) was used to quantify the age‐standardized mortality rate (ASMR) of viral hepatitis between 1990 and 2017. Globally, the number of deaths from viral hepatitis increased from 980.9 thousand in 1990 to 1412.3 thousand in 2017, accompanying by the DALYs increased from 35.2 million to 43.1 million in the same period. Hepatitis B and C accounted for 97.6% of total viral hepatitis‐related deaths worldwide in 2017. While the death number and DALYs were decreased in acute hepatitis A, B, C and E, a significant increase was found in liver cancer and cirrhosis due to hepatitis B and C. The ASMRs of liver cancer and cirrhosis caused by hepatitis B and C were decreased at the global level and in most regions. However, a significant increase was observed in several developed countries, such as the USA and the UK. The disease burden of viral hepatitis continues to increase worldwide, which was driven by the increase in burden of chronic hepatitis B and C.